Decreased biochemical progression in patients with castration-resistant prostate cancer using a novel mefenamic acid anti-inflammatory therapy: A randomized controlled trial - Guzman-Esquivel, José (Oncol Lett, 2020)
Prostate cancer (PCa) is the second most common non-dermatological cancer in men and is a growing public health problem. Castration-resistant disease (CRD) is the most advanced stage of the disease and is difficult to control. Patients with CRD may no longer accept conventional therapies as they are not in appropriate clinical conditions or they refuse to receive it. Given that inflammation is an essential component of CRD origin and progression, anti-inflammatory agents could be a therapeutic option with fenamates as one of the proposed choices. A prospective, randomized, double-blinded, 2-arm, parallel group, phase II–III clinical trial was performed involving 20 patients with CRD-PCa (with a prostate specific antigen level <100 ng/ml) that were undergoing androgen deprivation therapy (ADT) and did not accept any established treatment for that disease stage. In addition to ADT, 10 patients received placebo and 10 received mefenamic acid (500 mg orally every 12 h) for 6 months. The primary endpoint was the change in serum prostate-specific antigen (PSA) at 6 months. The PSA levels decreased significantly with mefenamic acid (an average 42% decrease), whereas there was an average 55% increase in the placebo group (P=0.024). In the patients treated with the placebo, 70% had biochemical disease progression (an increase of ≥25% in PSA levels), which did not occur in any of the patients treated with mefenamic acid (relative risk=0.12; 95% confidence interval, 0.01–0.85; P=0.033). There was a significant increase in quality of life (EQ-5D-5L score) and body mass index (BMI) with the experimental treatment. In conclusion, mefenamic acid administration decreased biochemical progression in patients with castration resistant PCa, improved their quality of life and increased their BMI. Future studies are required in order to strengthen the findings of the present clinical trial. Trial registration, Cuban Public Registry of Clinical Trials Database RPCEC00000248, August 2017.